Developing Digital Maze Literacy Game As Learning Media In Reading Instruction For Second Grade Of MA Al – Muhajirin Peterongan. - Nurul Afidah; Laili Romadona; Hanifah Hanifah (SCHOOLAR: Social and Literature Study in Education, 2021)
The aim of this study is to develop ‘Digital Maze Literacy’ in reading skills for students of MA Al – Muhajirin Peterongan. This product focused on analytical exposition text. The researcher chooses the ADDIE model in developing the product. This model consists of five steps. Those are: (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation.on develop phase, validation sheet was used to evaluate the quality of Digital Maze Literacy Game. The result of media validation is 80,00 % . Moreover the result of material validation is 81,3% , other word is very good category. Also, The result of the students responses on implementation phase is 82,3%. Based on the instrument, it can be concluded that Digital Maze Literacy game application for second grade of students has good quality and can be applied in real class.